Synthesis and characterization of nano potassium from green biomass and its impact on the growth, yield, and profitability of maize - M. V. Anjali; H. M. Jayadeva; Manjanagouda S. Sannagoudar; P. R. Somashekharappa; Akshay Kumar Kurdekar; G. A. Rajanna; V. Paramesha; Hanamant M. Halli; M. N. Harish (Discover Applied Sciences)
Abstract Despite the increasing demand for crops, potassium (K) fertilization in Indian agriculture remains inadequate, leading to severe potassium depletion and reduced crop productivity. A sustainable solution to this challenge is the use of green-synthesized nanopotassium fertilizers. In this study, potassium nanoparticles were synthesized using Azadirachta indica (neem) leaf extract and characterized through UV‒visible spectroscopy, particle size analysis, SEM, and SEM‒EDX. Their effects on maize growth and yield were evaluated under both pot and field conditions. Among the treatments, seed priming with 20 ppm nanopotassium for 45 min, combined with 100% recommended dose of potassium (RDK) and a foliar spray of 20 ppm nanopotassium, significantly improved key growth parameters—plant height (27.3%), leaf area index (19.6%), and total dry matter accumulation (31.2%)—compared to the 100% recommended dose of fertilizers (RDF) alone. This integrated treatment also resulted in a 29.2% increase in kernel yield (8519 kg ha⁻¹), along with enhanced nutrient use efficiencies: NUE (57 kg grain/kg N), PUE (114 kg grain/kg P), and KUE (332 kg grain/kg K). Economic analysis revealed a 39% higher net return (₹1,39,204 ha⁻¹) and a benefit–cost ratio of 3.25, validating the cost-effectiveness of this nanopotassium formulation. The findings highlight nanopotassium as a potent, eco-friendly alternative to conventional potassium fertilizers for improving maize productivity and profitability.